Fate of groundwater inflow in Lake Thingvallavatn during early spring ice-breakup - Hrund Ólöf Andradóttir 1972-; Forrest, Alexander; Laval, Bernard (2009)
Sub-artic Lake Thingvallavatn is one of Iceland´s largest, deepest and best known lakes. Situated at the rift between the North American and Eurasian tectonic plates, it is part of a world heritage site and a major tourist destination. From a hydrological viewpoint, the lake is unique in that it is predominantly fed by groundwater springs originating from nearby glacier Langjokull. The goal of this study was to establish the near field inflow dynamics of the largest subsurface spring Silfra, contributing approximately 30% of the total inflows to the lake, during early spring ice-breakup. A ten day field study was conducted in February 2009. The groundwater inflows were found to have higher temperature, conductivity, and pH than the receiving lake water. Using temperature as a tracer, the groundwater fate, and mixing regimes were assessed both in open water and under ice, as ice was breaking up and shifting in and out of the study area during the study period. Initial results from moored thermistor chains, CTD profiles, ADV measurements, weather stations and Autonomous Underwater Vehicle (AUV) borne CTD will shed a stronger light on the interaction of river inflows, ice cover and meteorological forcings during winter ice cover and early spring break-up. The use of an AUV platform to collect horizontal CTD profiles characterizes horizontal variability of water properties in open and ice-covered water, something that cannot be obtained using conventional techniques.